Effects of Different Zinc and Copper Concentrations in Soil on Morphological and Biochemical Properties of Ipomea aquatica: Zinc and Copper Effects on Ipomoea aquatica - Abd Manan, Fazilah; Ridzuan, Raihana; Henisi, Jessica; Prabakaran, Ashwini Nair (Journal of Tropical Life Science, 2023)
Zinc and copper pollution in agricultural lands due to anthropogenic activities has become a major environmental problem. While these metals are essential for plant growth, their excessive presence can lead to plant toxicity. This experiment aimed to investigate the effects of different concentrations of zinc and copper (0, 100, 200, and 300 ppm) in soil on the morphological and biochemical properties of I. aquatica, commonly known as water spinach. The morphological properties, including plant height, number of leaves, and stem diameter, were assessed, along with soil pH and electrical conductivity (EC). Biochemical properties, specifically the Total Phenolic Content (TPC) and Total Flavonoid Content (TFC) in plant tissues, were measured using colorimetric assays. The results revealed significant morphological changes in plant height, stem diameter, and number of leaves at 200 ppm zinc treatment compared to the control. Additionally, the number of leaves significantly increased at the 100 ppm copper treatment, while the stem diameter decreased significantly at 300 ppm. Both zinc and copper treatments slightly reduced soil pH and increased soil EC. At the 300 ppm treatment, substantial changes in phenolic and flavonoid contents were observed in the stems and leaves of I. aquatica. Copper treatment at 200 ppm increased the TPC of leaves, while 100 ppm copper treatment increased the TFC of stems. Furthermore, the 300 ppm zinc treatment significantly increased the TPC and TFC in stems and leaves. These findings indicate that zinc and copper concentrations have notable effects on the morphological and biochemical properties of I. aquatica. Therefore, it is crucial to maintain an appropriate balance of these metal elements to cultivate plants that are morphologically and physiologically resilient.